Improving the elimination of methyl orange dye by combining electrocoagulation system with the adsorption process by oven-dried alum sludge: adopting different combined systems - Mohammed Ali, Amor T.; Salman, Rasha H. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Due to their recalcitrant characteristics, Azo dyes such as methyl orange (MO) are extremely poisonous substances, making their removal from textile industry wastewater a major problem. By employing various EC-Adsorption combined system configurations and reusing alum sludge as an adsorbent, the current study seeks to investigate the efficiency of these various systems in removing MO dye. To estimate their benefits and limitations, experiments were carried out utilizing nickel foam (NiF) and aluminum plate (Al plate) as anodes, and stainless-steel mesh (SS mesh) as cathode in the presence of alum sludge as an adsorbent in all systems. The EC-Adsorption combined system with NiF as anode and two SS meshes as cathodes with 10 g/L of alum sludge in the solution, which is referenced as S3, offered 98.968% of MO dye removal efficiency within 30 minutes without the need for prolonged treatment and with very low concentration of leached Ni ions. The BET surface area, pore size, surface morphology, and composition of alum sludge were examined. The utilization of alum sludge in the combined system enhanced the removal of excess Ni ions and reduced its impact in the treated solutions, and moderately enhanced the MO dye removal efficiency. To attain a detailed explanation of the adsorption mechanism, various kinetics and isotherm models were applied. The adsorption of MO dye in the S3 EC-Adsorption system follows the intra-particle diffusion model, and the best-fit isotherm was the Freundlich isotherm.